Overcoming Anxiety Disorder by Probiotic Lactiplantibacillus plantarum LZU-J-TSL6 through Regulating Intestinal Homeostasis - Guanlan Liu; Israr Khan; Yuxi Li; Yun Yang; Xuerui Lu; Yafei Wang; Junxiang Li; Chunjiang Zhang (Foods, 2022)
Lactiplantibacillus plantarum LZU-J-TSL6 with high γ-aminobutyric acid (GABA) production (3.838 g/L) was screened and isolated from the Chinese fermented food snack “Jiangshui”. The improvement effect on anxiety disorder was explored using mice as animal models. In vitro results revealed that LZU-J-TSL6 had the potential to colonize the intestine (p < 0.01) and the anxiety-like behavior of the mice after seven days’ gavage with LZU-J-TSL6 was significantly improved (p < 0.01) when compared to the model group. LZU-J-TSL6 was able to effectively increase the GABA content in the mice hippocampus (p < 0.0001) and restore some markers related to anxiety such as brain-derived neurotrophic factor (BDNF), glial fibrillary acidic protein (GFAP), and 5-hydroxytryptamine (5-HT). Simultaneously, it had a certain repair effect on Nissl bodies and colon tissue in mice hippocampus. In addition, LZU-J-TSL6 increased the relative abundance of beneficial bacteria Bacteroides and Muribaculum, thereby regulating the imbalance of intestinal microbiota caused by anxiety disorder. It also affects the nerve pathway and intestinal mucosal barrier by increasing the content of glutamine and γ-aminobutyric acid and other related metabolites, thereby improving anxiety. Therefore, the GABA-producing Lactobacillus plantus LZU-J-TSL6 can be used as a probiotic to exert an indirect or direct anti-anxiety effect by maintaining the balance of the intestinal environment, producing related metabolites that affect nerve pathways and repair the intestinal mucosal barrier. It can be used as an adjuvant treatment to improve anxiety disorders.